Hyper-immunoglobulin E syndrome: Case series of 6 children from India - Rohit Kothari; Muneer Mohamed; K Vivekanandh; Sunmeet Sandhu; Preema Sinha; Anuj Bhatnagar (Wolters Kluwer Medknow Publications, 2023)
Hyper-immunoglobulin E syndrome is a rare primary immunodeficiency syndrome characterized by severe atopic dermatitis, recurrent pulmonary and staphylococcal skin infections. Its diagnosis requires a high degree of suspicion, typical clinical features, and not mere rise in serum IgE levels. Genetic studies are not always possible in a resource poor setting in developing countries. In this case series, all children had recurrent eczematoid rash, secondary infections, multiple episodes of hospitalization for pulmonary infection and raised serum IgE levels. Diagnostic genetic study was feasible in only one of the cases which revealed pathogenic homozygous deletions of exons 15 to 18 (Transcript: NM_203447) in DOCK8 gene. The main goal of management of hyper-immunoglobulin E syndrome is aggressive treatment of infections and optimum skin care. Our case series highlights various characteristic, presentations, and management of this rare syndrome childhood cases. Awareness of these manifestations may facilitate early identification and contribute to optimal care of patients as representative data on the same is limited in literature.